Functional volumetric analysis of striatum using F-18 FP-CIT PET in patients with idiopathic Parkinson’s disease and normal subjects - Jeong, Young Jin; Son, Hye Joo; Yoon, Hyun Jin; Kang, Do-Young (Annals of nuclear medicine, 2016)
Objective We applied a simple isocontour volume-of-interest (VOI) method to analyze the whole striatum in an F-18 FP-CIT PET image and to investigate the usefulness of the method in differentiating healthy subjects from idiopathic Parkinson’s disease (IPD) patients and the correlation of the value of functional volume parameters with the motor symptoms in patients with IPD. Methods Forty-three IPD patients and 23 age-matched healthy controls underwent F-18 FP-CIT PET. Using a dedicated workstation, VOIs for the whole striatum were drawn automatically with the gradient delineation method. The SUVmax, SUVmean, functional volume (FV), striatal volume activity (SVA), striatal-specific binding (SSB), and volume-specific uptake ratio (VSUR) were compared between the IPD patients and the normal subjects. In the IPD patients, the correlation between the clinical factor and the functional parameters was assessed. Results The SUVmax, SUVmean, FV, SVA, SSB, and VSUR were significantly lower in the IPD patients than in the normal subjects. In the receiver operating characteristic analysis, those parameters had significant and good-to-excellent accuracy. In the patients with IPD, a moderate negative correlation was revealed between the SUVmax and H&Y stage, the SUVmean and H&Y stage, SVA and H&Y stage, the VSUR and H&Y stage, the FV and bradykinesia, and the SVA and bradykinesia. Conclusion The functional volumetric analysis of the striatum based on simple isocontour VOI was a useful method of analyzing the F-18 FP-CIT PET image. Not only can it be easily applied in daily clinical practice, but it can also be used as a clinical parameter to discriminate IPD and to correlate it with the disease severity.